Delivering systems-level change to improve post-diagnostic dementia support: Qualitative findings from the PriDem study - Emily Spencer; Katie Flanagan; Marie Poole; Federica D’Andrea; Maud Hevink; Jane Wilcock; Kate Walters; Louise Robinson; Greta Rait; Sarah Griffiths (PLoS ONE, 2025)
Background There are 900,000 people with dementia in England and Wales. Existing models of post-diagnostic support are unsustainable and unaffordable. The PriDem programme developed a new model of primary care-based dementia care, whereby a Clinical Dementia Lead (CDL) would facilitate systems-level change. Aim To assess barriers and facilitators to implementation of the PriDem intervention. Methods 7 general practices participated in a qualitative process evaluation, as part of the mixed-methods feasibility and implementation study. Practices were located within 4 Primary Care Networks in the North East and South East of England. 26 healthcare professionals, 14 people with dementia and 16 carers linked to participating general practices participated in semi-structured individual and small group interviews. Additional qualitative data were generated through nonparticipant observations and researcher fieldnotes from CDL intervention supervision sessions. Data were analysed using abductive codebook thematic analysis informed by Normalisation Process Theory (NPT). Results Six themes were generated: 1) The rocky ground of primary care; 2) The power of people; 3) Tension between adaptability and fidelity; 4) Challenging the status quo: reimagining care planning; 5) One size doesn’t fit all; 6) Positive effects on people and systems: towards sustainability. Through the lens of NPT we can understand the contextual challenges facing primary care, the mechanisms (e.g., work undertaken by individuals) to overcome those challenges, as well as the potential outcomes of such an approach, in terms of longer-term sustainability of changes made. Conclusions Despite the pressures facing primary care within England and Wales, meaningful change can be made to practice in the care of people with dementia. The presence of motivated and engaged staff are critical to implementation, as is ensuring understanding of complex interventions, so that fidelity can be maintained. People with dementia and carers benefitted from improved care systems. Commissioners should consider the benefits of a CDL-led approach.